Effect of virtual reality training on dual-task performance in older adults: a systematic review and meta-analysis - Xiaoyu Wei; Chun Huang; Xinyue Ding; Zhining Zhou; Yufeng Zhang; Xiaofan Feng; Suwang Zheng; Tingting Li; Jiaojiao Lü (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Age-related decline in dual-task (DT) performance is closely associated with falls in older adults, posing a significant public health concern. Virtual reality (VR) training has emerged as a novel intervention to enhance motor-cognitive integration, yet its effects on dual-task performance require systematic evaluation. Objective The purpose of this systematic review and meta-analysis was to assess the impact of VR training on dual-task performance in older adults. Methods Following PRISMA guidelines, we searched four databases for randomized controlled trials (RCTs) evaluating VR training in adults aged ≥ 60 years. Inclusion criteria required comparisons between VR training and non-VR control groups, with outcome measures including dual-task cost (DTC), dual-task timed up-and-go (DT-TUG), DT gait parameters (speed, stride length, cadence), and DT cognitive performance. Methodological quality was assessed using the Cochrane Risk of Bias tool, and meta-analysis were conducted using RevMan 5.4. Results Twenty-one RCTs (935 participants) were included. Meta-analysis revealed significant improvements in VR groups for DTC of gait speed [SMD = -0.32, 95% CI (-0.57, -0.07), P = 0.01], stride length [SMD = -0.58, 95% CI: (-0.90 to -0.26), P < 0.001] and cadence [SMD = -0.32, 95% CI (-0.64, 0.00), P = 0.05]. DT-TUG time decreased significantly [SMD = -0.54, 95% CI (-0.89, -0.19), P = 0.002]. VR training also enhanced dual-task gait speed [SMD = 0.38 95% CI (0.03, 0.73), P = 0.03] and stride length [SMD = 1.15, 95% CI (0.81, 1.49), P < 0.001]. Subgroup analyses showed VR brought more notable improvements for MCI and PD patients. For VR interventions, durations over 1 h per session, more than 4 - week duration, and 3–5 sessions per week yielded better results. Yet, no significant improvements were observed in other DT aspects like cognitive reaction times and rapid gait speed. Conclusion VR training effectively reduces DT performance decline in older adults, particularly by lowering DTC and enhancing functional mobility, supporting its potential as a fall prevention strategy.